Effect of Irrigation on Growth of Three Tree Species in Indian Arid Zone - Bala, N; Singh, G; Bohra, N K (Annals of Arid Zone, 2016)
A trial was initiated in July 1995 to study the performance of Acacia nilotica, Eucalyptus cal7laldulensis and Dalbergia sissoo under two irrigation levels (WI = 30 mm and W2 = 45 mm) and three frequencies (1] = 0.2, 12 = 0.3 and 13 = 0.4) on a loamy sand soil. Irrigation schedule was maintained on the basis of IW/CPE ratio (irrigation water/cumulative pan evaporation). Average height of all three species was best (P<O.OI) in 13W2 treatment. In spite of receiving more irrigation water, the average height of plants in 13W] was less in comparison to plants in 13W2 treatment. Same trend was observed in case of collar girth and incremental growth. Variation in soil pH and electrical conductivity was also significant among the treatments. Results show that the quantity of water added per irrigation is more important than the total water applied. 13W2 treatment provided more soil volume with favorable moisture condition for roots which resulted in better growth.